2008
DOI: 10.1038/sj.bjc.6604222
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the antitumor activity of ionising radiation by nimotuzumab, a humanised monoclonal antibody to the epidermal growth factor receptor, in non-small cell lung cancer cell lines of differing epidermal growth factor receptor status

Abstract: The expression and activity of the epidermal growth factor receptor (EGFR) are determinants of radiosensitivity in several tumour types, including non-small cell lung cancer (NSCLC). However, little is known of whether genetic alterations of EGFR in NSCLC cells affect the therapeutic response to monoclonal antibodies (mAbs) to EGFR in combination with radiation. We examined the effects of nimotuzumab, a humanised mAb to EGFR, in combination with ionising radiation on human NSCLC cell lines of differing EGFR st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 38 publications
5
94
0
1
Order By: Relevance
“…To better understand the influence of the EGFR blockade on radiation response in GBM, we investigated the antitumour effect of combined treatment with two mAb to EGFR and radiation in human tumour U87MG xenografts. The antitumour effect of anti-EGFR mAbs in combination with radiotherapy has been thought to result from the enhancement of the inhibition of EGFR signalling, increasing the cytotoxic effect of the radiation (Akashi et al, 2008). Consistent with these results, we found that treatment with nimotuzumab and radiation enhanced the inhibition of EGFR-signalling activation, supporting a notion that the inhibition of ERK-mediated signalling is related to radiation response in vivo in GBM (Xia et al, 1995).…”
Section: Discussionsupporting
confidence: 89%
“…To better understand the influence of the EGFR blockade on radiation response in GBM, we investigated the antitumour effect of combined treatment with two mAb to EGFR and radiation in human tumour U87MG xenografts. The antitumour effect of anti-EGFR mAbs in combination with radiotherapy has been thought to result from the enhancement of the inhibition of EGFR signalling, increasing the cytotoxic effect of the radiation (Akashi et al, 2008). Consistent with these results, we found that treatment with nimotuzumab and radiation enhanced the inhibition of EGFR-signalling activation, supporting a notion that the inhibition of ERK-mediated signalling is related to radiation response in vivo in GBM (Xia et al, 1995).…”
Section: Discussionsupporting
confidence: 89%
“…The H292 lung cancer cell line was utilized due to its high level of EGFR and IGF-IR expression and its in vitro sensitivity to growth inhibition by anti-EGFR agents. 30,31 H292 also responds to stimulation with EGF and IGF ligands by activating EGFR and IGF-IR and downstream pathways. The increased activity of EI-Tandem compared to the monospecific Adnectins might be, in part, due to the differences in the positioning of PEG end groups in these molecules resulting from steric hinderance for binding to the EGFR or …”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Three lung cancer cell lines were selected based on the known status of EGFR (8,9), K-RAS, and TP53 (10) expression. A549 cells are known to express activated EGFR as a result of constitutive upregulation of autocrine/paracrine secretion of EGFR ligands, particularly ARG, and a resultant increase in p-EGFR.…”
Section: Cell Lines and Cell Culturementioning
confidence: 99%